Pengaruh Celebrity Endorser, Brand Image, dan Brand Trust terhadap Keputusan Pembelian Produk Scarlett Whitening - Shanfi Maylita Inggasari; Retno Hartati (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This research intends to find out how the influence of celebrity endorser, brand image and brand trust on purchasing decisions for Scarlett Whitening products, especially for women. Sampling with non-probability sampling method with purposive sampling technique. The number of samples in this research were 200 respondents and the data collection technique used a questionnaire. This research analysis includes validity test, reliability test, classical assumption test, F test, multiple linear regression analysis, t test and coefficient of determination (R²) test. The results of this research show that 1) celebrity endorsers have no effect on purchasing decisions for Scarlett Whitening products. 2) brand image has a positive and significant effect on purchasing decisions for Scarlett Whitening products. 3) brand trust has a positive and significant effect on purchasing decisions for Scarlett Whitening products. Adjusted R² of 0.731 or 73.1% which means celebrity endorser, brand image and brand trust have an influence of 73.1% on the purchasing decision variable, while 26.9% is influenced by other variables not included in the research model.